Investigating the social co-construction of masculinity(ies) and sexual development among very young male adolescents in Korogocho slum in Nairobi, Kenya - Maina, Beatrice Waitherero (My University, 2021)
Masculine norms as determinants of male sexuality and sexual health have been widely examined. Masculine norms are widely recognised as socially acceptable ways in which men should behave in a given society. However, few studies have examined gender norms among very young male adolescents (VYMA) (ages 10 – 14), and the influence of gender norms on sexual behaviours of these young boys. The purpose of this study was to investigate the social co-construction of masculinities and sexual development among VYMA aged 10 – 14 years living in Korogocho slum of Nairobi, Kenya and to examine how slum contexts shape the co-construction of masculinities and sexual development. This study looked at social co-construction of masculinities as a process in which boys’ individual characteristics interact with their social environment to inform their masculine beliefs and norms. Such masculine beliefs and norms, which are referred to as ”gender norms” in the study were measured using a scale developed and validated in the context of the Global Early Adolescent Study. Sexual experiences were considered a proxy for sexual development. Sexual experience was measured as lifetime experience of penetrative and/or non-penetrative sexual activities. Penetrative sexual activities, for this study, comprised penile-vaginal or penile-anal sexual intercourse while non-penetrative sexual activities included, spending time alone, holding hands, kissing, hugging/cuddling, touching, flirting over the phone, sharing personal sexual pictures and oral sex. The study was guided by the Bioecological theory of development to understand how different contexts within the boys’ ecosystem shaped their masculinity and sexual development. The study also used Connell’s theory of gender and power to understand how gender was structured in the study setting, separating roles and expectations for men/boys and women/girls, more so in romantic relationships. I conducted a cross-sectional study that utilised a sequential explanatory strategy to: 1) examine sexual experiences among VYMA aged 10 – 14 years; 2) examine the association between gender norms on sexual experiences and the contexts—individual, household, parental, peer and neighbourhood contexts—that shaped this association; and 3) to understand how boys co-constructed their masculinities, and; to assess whether masculinities were associated with sexual development. Data collection took place in December 2018 in Korogocho slum. The study was nested within the Nairobi Urban Health and Demographic Surveillance System, which provided a sampling frame. I collected quantitative data from a random sample of 426 boys and conducted in-depth interviews with 27 of these boys who were purposively selected based on reported sexual experience—eight boys with reported sexual experiences and 19 boys with no reported sexual experience. Twenty-two percent of boys who participated in the quantitative survey reported sexual experiences, with about 7% reporting sexual intercourse. There was a high endorsement of heteronormative gender beliefs about romantic relationships and low endorsement of sexual double standards. Sexual experience was inversely associated with low endorsement of heteronormative gender beliefs about romantic relationships. There was a statistically significant association between gender beliefs and sexual experiences even after controlling for individual and household level factors. Additionally, pubertal maturation, school absenteeism, being below recommended grade-for-age were significantly associated with a higher likelihood of reporting sexual experiences, while living in a household headed by someone aged 50 years and older, being born outside Nairobi and sharing a sleeping room with more than two people were significantly associated with a lower likelihood of reporting sexual experiences. The association between gender beliefs and sexual experience was diminished after controlling for parental and peer characteristics. Nevertheless, perceived parental approval of romantic relationships, often spending time with peers and having peers who were in romantic relationships were significantly associated with a higher likelihood of reporting sexual experiences. Results from the qualitative findings showed three bases of gender socialisation: 1) verbal messages; 2) observing older men in the society, and; 3) media. Boys conceptualized masculinity in reference to financial stability, family life and responsibility, physical attributes, character and religion. Boys depicted two divergent portrayals of masculinity —idealized masculinity with characteristics including family life and responsibility and financial stability; and dominant masculinities whose characteristics included violence, alcohol and substance use and sexual risk-taking. Boys perceived a close linkage between masculinity and sexual development, underscoring early sexual socialisation associated with prevailing sexual norms. Such sexual norms were associated with sexual risk-taking including early sexual debut andsexual infidelity within the contexts that boys lived. This study has contributed to the emerging evidence on the association between gender norms and VYMA’s sexual development. The findings show that in the study setting, sexual activity begins at an early age, albeit at a small magnitude and highlights the existence of sexual expressions beyond penetrative sexual activity. In this regard, the study highlights the importance of focusing on non-penetrative sexual activities as they are important for understanding sexual development. Although the study shows that inequitable gender norms are learnt early, the results suggest that in early adolescence, these norms are yet to translate into behaviour that promotes early sexual activity.. As such, early adolescence offers a window of opportunity to reach young people before inequitable gender norms influence risky behaviour. Beyond gender norms, the study highlights different contexts, such as the role of parents, peers, and the neighbourhood characteristics that shape sexual development. This implies that addressing the sexual health needs of adolescent boys should go beyond individual-level factors and focus on contexts within the boys’ ecosystems.
This PhD thesis is submitted to the School of Public Health, Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, South Africa, as partial fulfilment of the requirements for the degree of Doctor of Philosophy, September 2021